1995
DOI: 10.1007/bf01581574
|View full text |Cite
|
Sign up to set email alerts
|

Binding of adenine and adenine-related compounds to the clay montmorillonite and the mineral hydroxylapatite

Abstract: The first living things may have consisted of no more than RNA or RNA-like molecules bound to the surfaces of mineral particles. A key aspect of this theory is that these mineral particles have binding sites for RNA and its prebiotic precursors. The object of this study is to explore the binding properties of two of the best studied minerals, montmorillonite and hydroxylapatite, for possible precursors of RNA. The list of compounds investigated includes purines, pyrimidines, nucleosides, nucleotides, nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 29 publications
3
59
0
Order By: Relevance
“…surface adsorption sites. However, conditions exist where mixtures of different bases can coexist on a surface, presumably because of their ability to interact with each other by hydrogen bonding (15,23). The physical origin of this disparate behavior is contributed to by molecular differences in the van der Waals surface area of the bases (15) and variability in their solubility in water (g͞100 ml Temp Electrochemical measurements made at the mercury-water interface show that maximal adsorption of the bases occurs at the potential of zero charge (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…surface adsorption sites. However, conditions exist where mixtures of different bases can coexist on a surface, presumably because of their ability to interact with each other by hydrogen bonding (15,23). The physical origin of this disparate behavior is contributed to by molecular differences in the van der Waals surface area of the bases (15) and variability in their solubility in water (g͞100 ml Temp Electrochemical measurements made at the mercury-water interface show that maximal adsorption of the bases occurs at the potential of zero charge (30).…”
Section: Resultsmentioning
confidence: 99%
“…The purine and pyrimidine bases adsorb spontaneously from aqueous media onto inorganic solids and have been observed on the surfaces of graphite (17)(18)(19)(20)(21), MoS 2 (15,(18)(19)(20)(21), crystalline gold (22), and clays (23,24). Scanning probe microscopy (SPM) studies have shown that the bases are planar-arranged on these surfaces like jigsaw puzzle pieces.…”
mentioning
confidence: 99%
“…The extent of adsorption was primarily influenced by the acid dissociation constant of the nucleic acid base. Winter and Zubay (1995) investigated the relative ability of montmorillonite and hydroxylapatite in adsorbing adenine and adenine-related compounds [35]. They found that montmorillonite adsorbed more adenine than the other compounds (adenosine, 5'-AMP, 5'-ADP, 5'-ATP), while hydroxylapatite preferred adenosine phosphate to adenine and adenosine.…”
Section: Adsorption Of Nucleic Acid Bases By Clay Mineralsmentioning
confidence: 99%
“…The adsorption of nucleic acid bases was studied in the following minerals: clays (Lailach et al 1968;Lailach and Brindley 1969;StrašáK 1991;Weckhuysen et al 1999;Perezgasga et al 2005;Hashizume and Theng 2007;Benetoli et al 2008;Hashizume et al 2010;Negrón-Mendoza et al 2010;Pucci et al 2010), apatite (Winter and Zubay 1995), silicon dioxide (Plekan et al 2007), graphite (Sowerby et al 2001a, b), metals sulfide compounds (Sowerby et al 1998;Bebié and Schoonen 2000;Plekan et al 2007;Hatton and Rickard 2008) and rutile (Cleaves et al 2010).…”
Section: Introductionmentioning
confidence: 99%